(untitled) (Journal of Nobel Medical College, 2023)
Background: Thyroid disorders (TD) are the second most common endocrine disorders seen in pregnancy. TD is known to be associated with adverse maternal and fetal outcomes. Materials and Methods: This was a hospital based descriptive cross-sectional study. All the pregnant women attending the antenatal clinic at Birat Medical College Teaching Hospital from 1st July 2021 to 30th June 2022 were enrolled in the study, irrespective of their gestational age and gravida status. Pregnant women with diagnosed thyroid disorder and are on medication, multiple gestation, Diabetes mellitus, Hypertension and pregnant women with age more than 35 years were excluded from study. Thyroid function status of pregnant women was assessed by measuring serum levels of thyroid stimulating hormone (TSH) and if the TSH value was deranged then they underwent free T3 and free T4 level. Based on the TFT reports they will be classified as euthyroid, subclinical hypothyroidism and overt hypothyroidism, subclinical hyperthyroidism and overt hyperthyroidism. Results: A total of 395 pregnant women were enrolled in this study. The mean age and standard deviation of pregnant women was 25.25± 4.76 years. Among 395 pregnant women 93(23.6%) pregnant women have thyroid disorder. Subclinical hypothyroidism and Overt hypothyroidism were 19% and 1.8% respectively. Subclinical and Overt hyperthyroidism were 1.5% and 1.3% respectively. Conclusion: The prevalence of thyroid disorder in pregnancy was 23.6%. The most common thyroid disorder observed was Subclinical hypothyroidism comprising 19% cases followed by overt hypothyroidism comprising 1.8% cases followed by Subclinical and Overt hyperthyroidism 1.5% and 1.3% cases respectively.